2017
DOI: 10.1589/jpts.29.232
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Berg Balance Scale and Fullerton Advanced Balance Scale to predict falls in community-dwelling adults

Abstract: [Purpose] The purpose of this study was to investigate and compare the predictive properties of Berg Balance Scale and Fullerton Advanced Balance Scales, in a group of independently-functioning community dwelling older adults. [Subjects and Methods] Ninety-seven community-dwelling older adults (male=39, female=58) who were capable of walking independently on assessment were included in this study. A binary logistic regression analysis of the Berg Balance Scale and Fullerton Advanced Balance Scale scores was us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 10 publications
1
9
0
Order By: Relevance
“…The findings showed that both cognitive functions and balance abilities significantly declined as people aged. In line with the outcomes of other studies, the current finding also indicates that community-dwelling elderly individuals with mild cognitive impairment 9 , 13 , 33 , 34 and balance impairment 20 , 31 , 34 were most at risk of falling. From the aging perspective, deteriorating speed of cognitive function, a decline in attention and executive function (eg, slow response inhibitions and judgment errors), and declines in sensory systems, due to the aging of the frontal cortex, could be the biggest factors for an increased risk of falling.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The findings showed that both cognitive functions and balance abilities significantly declined as people aged. In line with the outcomes of other studies, the current finding also indicates that community-dwelling elderly individuals with mild cognitive impairment 9 , 13 , 33 , 34 and balance impairment 20 , 31 , 34 were most at risk of falling. From the aging perspective, deteriorating speed of cognitive function, a decline in attention and executive function (eg, slow response inhibitions and judgment errors), and declines in sensory systems, due to the aging of the frontal cortex, could be the biggest factors for an increased risk of falling.…”
Section: Discussionsupporting
confidence: 91%
“…On the other hand, the BBS tool produced the highest sensitivity in predicting falls in independent functioning, community-dwelling elderly individuals. 30 , 31 However, Muir et al 16 found that the BBS tool, with the cutoff value at 45, failed to identify people at a high risk of falling (multiple falls). They suggested that the use of a scale cutoff point of 45, suggested by Berg et al, 15 was inadequate to predict future falls.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…BBS can reflect the degree of walking improvement for patients with stroke, [ 48 ] and predict the risk of falls. [ 49 ] All in all, it is suggested that BW can be used as an effective method to improve some gait indices, balance and walking ability of stroke patients.…”
Section: Discussionmentioning
confidence: 99%